Fabrication And Properties Of Silicaepoxy Thin Film Composite - Foo , Yin Lin Evon (2012)

(untitled)
With the increasing interest in high density electronics packaging, dimensional scaling becomes the key to evolution. In this study, epoxy thin film composites with silica fillers were fabricated using spin coating process. In the first part of this research, the mechanical and thermal properties of the thin film composites using micron-silica (µ-Si) and nano-silica (n-Si) fillers were compared. Low loading of n-Si thin film composites was found to have the ability to achieve equivalent tensile and thermal properties compared to the highly loaded µ-Si thin film composite. With higher surface area to volume ratio, n-Si shows its capability to achieve a substantial performance with -Si. In terms of curing agents, imidazole cured thin film was found to have better mechanical and thermal properties due to the presence of five membered ring in the imidazole chemical structure. The moisture absorption of the imidazole cured samples were slightly higher than the polyetheramine cured samples because imidazole cured resin is a polar resin. The dispersion of the n-Si filler was improved by the treatment of n-Si with (3-Glycidyloxypropyl) trimethoxysilane coupling agent. It was observed that 8 hours treatment time showed high mechanical properties of the thin film composites. Prolong treatment time caused the drop in tensile modulus and tensile strength but increase the flexibility of the thin film composites. The presence of treated n-Si in the composite system causes the increase in the coefficient of thermal expansion (CTE) value and lowers the thermal stability compared to the untreated n-Si thin film composites. However, treatment of the n-Si was found to cause the modification of the hydrophilic n-Si surface into a hydrophobic surface, thus reduced the moisture absorption of the thin film composites.